Generating Hexahedral Mesh for Wire-wrapped Fuel Assembly With RBF Mesh Deformation Method - Wang, X. A.; Zhang, Dalin; Wang, Mingjun; Liu, Yapeng; Zhou, Lei; Wang, Shibao; Liang, Yu; Tian, Wenxi; Qiu, Suizheng; Su, G. H. (Frontiers in Energy Research, 2021)
Fuel assemblies with wire spacer are widely used in Generation IV liquid nuclear reactors. With the rapid development of computational power, the Computational Fluid Dynamic (CFD) method is becoming an effective tool to investigate the detailed three-dimensional thermal hydraulic characteristics in wire-wrapped fuel assemblies. Due to the complexity of geometry, most of the published researches are performed with large number tetrahedron or polyhedral cells. The simulation is quite time-consuming and is generally limited to assemblies with small number of fuel pins. In this paper, a hexahedron meshing strategy is developed based on the Radial Basis Function (RBF) theory in present paper. This strategy would be beneficial for the modeling for the wire-wrapped fuel assemblies in real nuclear reactor core with large number of fuel pins. To validate this strategy, two experiments are simulated and detailed flow parameter distributions within the bundle, including the pressure distribution and the temperature distribution, have been compared. Good agreements have been achieved between the simulation results and the experimental results.